Effect of xylitol and casein phosphate amorphous calcium phosphate gums on saliva: A randomized clinical trial - Zahra Bahrololoomi; Golnaz Malihi; Mohammad Mazloum Ardakani; Arezoo Ghotbzadeh; Maryam Irannezhad (Mashhad University of Medical Sciences, 2024)
Objective: This study aimed to investigate the effects of two types of gum, containing xylitol or casein phosphopeptide-amorphous calcium phosphate (CPP-ACP), on saliva properties.Methods: In this single-blind clinical trial, 60 dental students were randomly divided into three groups (n=20). Each group was instructed to chew one of the following substances: paraffin (control), xylitol gum, or CPP-ACP gum. Saliva samples were collected before and five minutes after chewing. Saliva volume was measured using a pipette, and saliva pH was evaluated with a digital pH meter. The calcium concentration was determined using the photometric method, while phosphorus concentration was measured via spectrophotometry. Statistical analysis was performed using the chi-square test, ANOVA, Tukey HSD post hoc test, and paired t-test (α = 0.05).Results: Chewing all three substances significantly increased saliva volume and pH while reducing phosphorus ion concentration (P < 0.05). The calcium ion level increased significantly after five minutes of chewing the CPP-ACP gum (P = 0.002). After the intervention, between-group comparisons revealed no significant difference in saliva volume and pH (P > 0.05). However, the calcium level in the CPP-ACP group was significantly higher than the control group (P = 0.01). Additionally, the phosphorus ion level was significantly lower in the xylitol gum group than in the control and the CPP-ACP groups (P < 0.05).Conclusions: Chewing CPP-ACP gum may promote oral health more effectively than xylitol gum by increasing salivary calcium levels and less affecting phosphorus levels.